Exploring Multivalent Architectures for Binding and Stabilization of N-Acetylgalactosamine 6-Sulfatase - Maria Giulia Davighi; Francesca Clemente; Giampiero D’Adamio; Macarena Martínez-Bailén; Alessio Morano; Andrea Goti; Amelia Morrone; Camilla Matassini; Francesca Cardona (Molecules)
Morquio A syndrome is a lysosomal disorder caused by the deficiency of the lysosomal enzyme N-acetylgalactosamine 6-sulfatase (GALNS, EC 3.1.6.4). Currently, enzyme replacement therapy (ERT) is used to treat Morquio A through the infusion of the recombinant enzyme VIMIZIM® (elosulfase alfa, BioMarin). Unfortunately, the recombinant enzyme exhibits low conformational stability in vivo. A promising approach to address this issue is the coadministration of recombinant human GALNS (rhGALNS) with a pharmacological chaperone (PC), a molecule that selectively binds to the misfolded protein, stabilizes its conformation, and assists in the restoration of the impaired function. We report in this work the synthesis of a library of multivalent glycomimetics exploiting the copper(I)-catalyzed azide-alkyne cycloaddition (CuAAC) reaction between several dendrimeric scaffolds armed with terminal alkynes and azido ending iminosugars of different structures (pyrrolidines, piperidines, and pyrrolizidines) or simple azido ending carbohydrates as bioactive units. The biological evaluation identified pyrrolidine-based nonavalent dendrimers 1 and 36 as the most promising compounds, able both to bind the native enzyme with IC50 in the micromolar range and to act as enzyme stabilizers toward rhGALNS in a thermal denaturation study, thus identifying promising compounds for a combined PC/ERT therapy.